American Civil War guerrillas : changing the rules of warfare - Sutherland, Daniel E. (Reflections on the Civil War era, 2013)
"Focusing on a little-known yet critical aspect of the American Civil War, this must-read history illustrates how guerrilla warfare shaped the course of the war and, to a surprisingly large extent, determined its outcome"--